Adaptations and transformations of hunter-gatherers in forest environments: New archaeological and anthropological insights. (October 2019) - Groß, Daniel; Piezonka, Henny; Corradini, Erica; Schmölcke, Ulrich; Zanon, Marco; Dörfler, Walter; Dreibrodt, Stefan; Feeser, Ingo; Krüger, Sascha; Lübke, Harald; Panning, Diana; Wilken, Dennis
Like any other living being, humans constantly influence their environment, be it intentionally or unintentionally. By extracting natural resources, they shape their environment and also that of plants and other animals. A great difference setting people apart from all other living beings is the ability to construct and develop their own niche intentionally, and the unique tool for this is cultural behaviour. Here, we discuss anthropogenic environmental changes of hunter-gatherers and present new palaeoecological and palynological data. The studies are framed with ethnoarchaeological data from Western Siberia to gain a better understanding of how different triggers lead to coping mechanisms. For archaeological implication, we use two Mesolithic case studies from Germany: One of them focuses on hazelnut economy around ancient Lake Duvensee, and the other broaches the issue of selective roe deer hunt and its consequences at the site of Friesack. We address the archaeological evidence from the perspective of active alteration and its consequences, starting our argumentation from a perspective of niche construction theory. This approach has rarely been applied to early Holocene hunter-gatherers in Northern Europe even though the available data render possible to discuss human–environment interaction from such a perspective. It is demonstrated that archaeological research has tools at hand that enables to detect anthropogenic niche construction. However, the ethnoarchaeological example shows limitations and archaeologically invisible triggers and consequent results of human adaptations. The critical revision of such perspectives based on empirical data provides a better understanding of social and environmental transformations in the early- and mid-Holocene.